Virtual Twin in Healthcare - Gongate, Suhaspritpal Danaiah (Digital Repository of Theses, 2024)
This research study focuses on the comprehensive examination of virtual twin technology within the healthcare domain, a rapidly advancing field with far-reaching implications. Leveraging a blend of virtual and physical worlds, virtual twin technology offers real-time simulations and monitoring of healthcare systems. Despite its immense potential, including enhanced patient care, personalized medicine, and predictive analytics, the technology's widespread adoption faces challenges, including technical barriers, ethical concerns, and financial constraints. This study aims to explore the feasibility, applications, impact, opportunities, and challenges of virtual twin technology in healthcare. Employing a qualitative approach, the investigation encompasses an analysis of existing literature, expert opinions, and real-world implementation examples. The objectives include an in-depth evaluation of how virtual twin technology can revolutionize patient engagement, clinical decision-making, healthcare outcomes, and the formulation of effective frameworks and guidelines. The findings of this research may serve as a vital guide for healthcare providers, policymakers, researchers, and technology developers. This study not only bridges the existing knowledge gap but also lays the groundwork for future research, technology development, and policy formulation, contributing to the successful integration and utilization of virtual twin technology in the healthcare sector.